2019
DOI: 10.1093/eurheartj/ehz584
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of heart failure after pacemaker implantation: a nationwide Danish Registry-based follow-up study

Abstract: Aims The objective of the current study is to investigate the risk of heart failure (HF) after implantation of a pacemaker (PM) with a right ventricular pacing (RVP) lead in comparison to a matched cohort without a PM and factors associated with this risk. Methods and results All patients without a known history of HF who had a PM implanted with an RVP lead between 2000 and 2014 (n = 27 704) were identified using Danish natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 27 publications
6
61
1
9
Order By: Relevance
“…Meta‐analysis also suggests that the longer the period of pacing the more likely LV dysfunction will occur . In contrast a recent publication suggested that clinical heart failure occurred as early as within 30 days . Overall the data is not consistent but in the main the longer the pacing duration the more likely PICM will occur.…”
Section: Factors Not Related To Lead Positionmentioning
confidence: 93%
See 4 more Smart Citations
“…Meta‐analysis also suggests that the longer the period of pacing the more likely LV dysfunction will occur . In contrast a recent publication suggested that clinical heart failure occurred as early as within 30 days . Overall the data is not consistent but in the main the longer the pacing duration the more likely PICM will occur.…”
Section: Factors Not Related To Lead Positionmentioning
confidence: 93%
“…Intriguingly, 8.5% of patients in this study showed an improvement in LVEF following RVp. A recent observational registry study of 35,389 patients implanted with an RV lead showed a cumulative incidence of heart failure (HF), including fatal HF, in 10.6% …”
Section: What Is the Size Of The Problem Of Left Ventricular Dysfunctmentioning
confidence: 99%
See 3 more Smart Citations